Model Intensi UMKM dalam Mengadopsi Layanan Pinjaman Online (Financial Technology Lending) - Tria Apriliana; Gusni Gusni; Lilik Farida (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
MSME in Indonesia is a sector that is proven to be able to survive in all critical conditions when the national economy is disrupted. However, MSME business development is often hampered by access to capital. The industrial revolution 4.0 opens opportunities for access to capital for MSMEs, which cannot be accommodated by conventional financing institutions such as banks or cooperatives. Financial technology (Fintech) allows MSMEs to have access to capital with easier conditions than conventional institutions but with higher risks. This study aims to determine the effect of subjective norms, perceived behavioral control, financial literacy, risk perception, perceived ease of use, perceived usefulness, interest rate, and social influence on intentions to use online loan applications, as well as the implications for actual system use of the application. online loans. The study used a sample of 200 MSME business actors in West Java who used fintech. The sampling technique used is purposive random sampling. The analytical method used is path analysis. The results of the analysis show that Perceived behavioral control, financial literacy, and perceived ease of use influence the intention to use the application. Intention to use the application also affects actual system use. In addition, perceived behavioral control, financial literacy, and perceived ease of use affect actual system use through intention to use.